Role of Iron Deficiency in Chronic Hair Loss - R. Ananya1 , M. P. Brundha2 , D.Ezhilarasan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Anemia is a condition in which you lack enough healthy red blood cells to carry sufficient oxygen into thetissues of your body. Anemia can make you feel weak and tired. Iron deficiency anemia is the most commonform of anemia, which occurs when there is not enough mineral iron in your body. To generate hemoglobinyour body needs iron. If your blood supply doesn’t have enough iron, the rest of the body can’t get theamount of oxygen it needs.Hair is a fast-proliferating organ with a high blood supply requirement. Thelength and size of the hair depend on the hair cycle anagen, growth stage. At the center of these systems,however, lies the blood supply in the scalp, the oxygen delivery system, and nutrients that are provided to thesubcutaneous blood flowing hair follicles. It is not yet clear what role iron plays in hair loss. This researchhad the purpose of determining the relationship between iron and hair loss. Iron hair loss deficiency maylook like traditional hair loss patterned by males and females. A study published in the Journal of KoreanMedical Science found that iron may not only play a role in hair loss, but may also cause hair to fall out ina manner similar to genetic baldness of male and female patterns. The aim of the study is to analyse the roleof iron deficiency in chronic hair loss. Most widely cited nutritional causes of hair loss include iron, one ofthe key micronutrients in metabolism of our body. This review gives a clear knowledge about the differentroles played by iron deficiency in the body, specifically its role in chronic hair loss.